Short-term solar power forecasting using similar condition approach based on euclidean distance with weighted coefficients - Sun, Haiguang. (2014)
As a renewable source, solar power presents great potential for applications in power systems. However, due to the randomness of the weather condition, solar power output cannot keep steady. Accordingly when a solar photovoltaic (PV) unit is connected to the grid, it will cause frequency deviation in the power system and if the injection level is high, it can be a serious problem in terms of power quality. Hence it is necessary and important to find a way to make short-term forecasting for solar power.